Reframing money politics in local electoral debates: evidence from Southern Sulawesi, Indonesia - Hasan Sazali; Hayat, Nahrul (Faculty of Communications Science, Dr. Soetomo University, 2026)
Local mayoral debates fulfil a strategic function in shaping public perceptions of political agendas and democratic processes at the subnational level. Empirical research on candidates' framing of public issues in formal debate contexts within Indonesian local elections remains scarce. This study redresses this lacuna through a qualitative framing analysis of the 2024 mayoral election debates in Makassar and Parepare—two urban centres in South Sulawesi exhibiting distinct political dynamics. Drawing on debate transcripts from official recordings, the analysis elucidates how candidates select, emphasise, and organise interpretive frames in articulating public policy issues. A systematic coding procedure, grounded in established framing typologies, was employed. The findings delineate three interrelated pathways: economic narratives that moralise welfare; digital narratives equating transparency with integrity; and moral narratives converting piety into political capital. These symbolic substitutions evince the endurance of symbolic patronage in contemporary discursive forms, conceptualised herein as a discursive moral economy of democracy. Theoretically, the study reconceptualises money politics as a representational mechanism for legitimacy construction, rather than merely a behavioural practice.